The modification of some properties of Al-2%Mg alloy by Ti &Li alloying elements (Journal of University of Babylon for Engineering Sciences, 2017)
Aluminium-Magnisium alloys are light, high strength with resistance to corrosion and good weldability. When the content of magnesium  exceeds 3% there is a tendency to stress corrosion .This work is an attempt is to prepare low density alloy with up to approximately 2.54 g / cm3 by adding different contents of Ti, and lithium to aluminum-2%Magnisium alloy. The lithium is added in two aspects, lithium chloride and pure metal. The casting performed using conventional casting method. Moreover, solution heat treatment (SHT) at 520 ºC for 4 hrs, quenching in cold water, and aging at 50ºC for 4 days were done to get better mechanical properties of all samples. Microstructure was inspected by light optical microscope before and after SHT. Alloy3 which contains 1.5%Ti was tested by SEM and EDS spectrometer to exhibit the shape and micro chemical analysis of Al3Ti phase. Hardness, ultimate tensile strength, and modulus of elasticity were tested for all alloys. The results indicated that Al3Ti phase precipitates in alloys contain 0.5%T, 1%Ti, And 1.5%Ti.  The phases Al3Li as well as Al3Ti were precipitated in alloy4 which contains 2%Ti, and 2.24%Li. Mechanical properties test results also showed that the alloy4 has achieved good results, the modulus of elasticity chanced from 310.65GPa before SHT to 521.672GPa, after SHT and aging, the ultimate tensile strength was changed from 365MPa before SHT to 469MPa, after SHT and aging,  and hardness was increased from 128 to 220HV.